2023
DOI: 10.3390/ijms24043574
|View full text |Cite
|
Sign up to set email alerts
|

Role of the MicroRNAs in the Pathogenic Mechanism of Painful Symptoms in Long COVID: Systematic Review

Abstract: The ongoing pandemic of COVID-19 has caused more than 6.7 million tragic deaths, plus, a large percentage of people who survived it present a myriad of chronic symptoms that last for at least 6 months; this has been named as long COVID. Some of the most prevalent are painful symptoms like headache, joint pain, migraine, neuropathic-like pain, fatigue and myalgia. MicroRNAs are small non-coding RNAs that regulate genes, and their involvement in several pathologies has been extensively shown. A deregulation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Interestingly, from this list miR‐15a‐5p and miR‐31‐5p appeared in two or more studies 56,57,73,78,82,84,86 and could potentially serve as biomarkers for disease severity. Table 3 summarises the targets and principle cellular pathways associated with miRNAs regulated during Inf vs C and S vs C stages and cited previously 46,56,73,88–120 . Most of the miRNAs were involved in targeting virus‐host interactions, viral replication, and host‐immune responses.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, from this list miR‐15a‐5p and miR‐31‐5p appeared in two or more studies 56,57,73,78,82,84,86 and could potentially serve as biomarkers for disease severity. Table 3 summarises the targets and principle cellular pathways associated with miRNAs regulated during Inf vs C and S vs C stages and cited previously 46,56,73,88–120 . Most of the miRNAs were involved in targeting virus‐host interactions, viral replication, and host‐immune responses.…”
Section: Resultsmentioning
confidence: 97%
“…In a systematic review by Reyes-Long et al (2023), they have demonstrated that microRNA expression levels differ between COVID-19 positive and negative patients, and these differences may be associated with the upregulation or downregulation of specific microRNAs 55 . Additionally, in the study by Shi et al (2022), differences in microRNA expression among patients are observed 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Of all miRNAs, hsa-miR-29b-3p appears to wield a potent regulatory in uence on the advancement of OA 39 . The miRNAs hsa-miR-29a,b,c-3p might be intricately linked to the pathogenic process of SARS-CoV-2 infection via engagement with the IL-6/STAT3 pathway 40 . Research has demonstrated a potential close correlation between hsa-miR-145-5p and the growth of airway smooth muscle cells, which could potentially in uence the prognosis of patients with COVID-19 41 .…”
Section: Discussionmentioning
confidence: 99%